1997
DOI: 10.1097/00005768-199704000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ischemia and reperfusion injury following exercise training

Abstract: We examined the effects of two exercise training modalities, i.e., low-intensity endurance and sprint running, on in vitro, isovolumic myocardial performance following ischemia and reperfusion. Rats ran on a treadmill 5 d.wk-1 for 6 wk at the following levels: endurance; 20 m.min-1, 0% grade, 60 min.d-1 and sprint; five 1-min runs at 75 m.min-1, 15% grade interspersed with 1-min active recovery runs at 20 m.min-1, 15% grade. Both endurance and sprint training significantly improved exercise tolerance relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 29 publications
5
57
2
Order By: Relevance
“…In the present study, hearts obtained from endurance exercise-trained animals exhibited a better recovery of contractile function after a brief period of ischemia and reperfusion than hearts obtained from sedentary rats. In agreement with the present study, some studies have reported that exercise training elicited an improved functional recovery, as measured in whole hearts, in response to ischemia-reperfusion (6,7,19,22,24), whereas other studies did not (19,21). These conflicting results may result from diverse experimental protocols (e.g., ischemic duration, global vs. regional ischemia), as well as differences in exercise protocols.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, hearts obtained from endurance exercise-trained animals exhibited a better recovery of contractile function after a brief period of ischemia and reperfusion than hearts obtained from sedentary rats. In agreement with the present study, some studies have reported that exercise training elicited an improved functional recovery, as measured in whole hearts, in response to ischemia-reperfusion (6,7,19,22,24), whereas other studies did not (19,21). These conflicting results may result from diverse experimental protocols (e.g., ischemic duration, global vs. regional ischemia), as well as differences in exercise protocols.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, experimental studies have documented that both short-and long-term endurance exercise provides myocardial protection against ischemia-reperfusion injury in rats (6,14,23,30,53,54,77). Several factors, including an increase in calcium handling (14), endogenous antioxidants (50,77), heat shock proteins (50,81), and increased expression of myosin heavy chain-␤ (34) as well as intrinsic metabolic factors and reduced content of the arrhythmogenic substance cyclic AMP, have been implicated as mechanisms responsible for the protective effects of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…126 -128 Studies that use less intense training programs have not consistently observed protection from ischemia and reperfusion. 124,127,129,130 In summary, in the majority of clinical and experimental studies, endurance-type exercise training has improved indices of diastolic function in elderly and younger humans and in rats with LVH. Thus, exercise training may have beneficial potential in clinically significant, symptomatic diastolic dysfunction.…”
Section: Long-term Exercise Training and Protection Against Hypoxic Amentioning
confidence: 97%